Expanding the Clinical and Molecular Spectrum of PSMD12-Related Neurodevelopmental Syndrome: An Additional Patient and Review - Palumbo, Pietro; Palumbo, Orazio; Muro, Ester Di; Leone, Maria Pia; Castellana, Stefano; Biagini, Tommaso; Mazza, Tommaso; Leotta, Valentina; Carella, Massimo; Bukvic, Nenad (Archives of Clinical and Medical Case Reports, 2019)
Degradation of proteins by the ubiquitin-proteasome system (UPS) is an essential biological process that eukaryotic cells use to regulate their functions and coordinate their signaling networks. In particular, it plays a crucial role in neuronal development regulating very important functional and morphological interplays of neurons, such as synaptic plasticity, neurotransmitter release and morphogenesis of axons. Pathogenic alterations of genes involved in the proteolysis by UPS have been associated with several neurodevelopmental disorders (NDDs) and human diseases, highlighting the importance of this regulatory mechanism to developmental processes and neurogenesis. Here, we describe a 19 years old male patient showing a syndromic form of NDD. The main clinical features are intellectual disability/speech delay, congenital anomalies and facial dysmorphisms. Through a targeted resequencing approach (TRS), we identified a missense variant in PSMD12, a gene recently associated to an emerging syndromic form of NDD, which encodes for the non-ATPase subunit of the 19S regulator of 26S proteasome complex. The variant described herein, inherited from the father with apparently borderline cognitive ability, is useful to expand the molecular spectrum of heterozygous PSMD12 mutations and to provide insight into the molecular pathogenesis of this new condition since it is, to the best of our knowledge, the first missense substitution to date reported in medical literature. More importantly, our study highlight once again the utility of next generation sequencing in establishing an etiological basis in clinically and genetically heterogeneous conditions such as NDDs, thus allowing a better diagnosis, counseling and management of affected patients and their families.